PHOTOCHEMICAL SELF-PURIFICATION OF AQUATIC SYSTEMS IN THE PRESENCE OF VITAMIN B₆ - GLADCHI, Viorica; BLONSCHI, Vladislav; DUCA, Gheorghe; LIS, Angela; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2026)
Vitamin B6 (pyridoxine, PN) released from anthropogenic and biogenic activities can influence the chemical self-purification of surface waters through its photochemical transformations. The present study aimed to investigate the kinetics and mechanisms of pyridoxine photodegradation under conditions that partially simulate the natural environment (pH 7, aerated medium) using simulated solar irradiation. Three model systems were investigated: (1) PN–hν; (2) PN–H2O2–hν; (3) PN–H2O2–Cu(II)–hν, using direct spectrophotometry (λ = 328 nm). The kinetic parameters determined included partial reaction orders (using the van’t Hoff method), effective rate constants, and half-lives (τ₁/₂). Direct photolysis of PN follows a partial reaction order of 0.2 with respect to [PN], with k = (5.38±0.26)·10-4 s-1 and τ₁/₂ = 21±0.5 min. However, the low quantum yields (7.31–10.70)·10-3 indicate that direct photolysis of vitamin B6 is negligible under natural aquatic conditions. In the presence of H2O2, the partial reaction orders are 0.3 (PN) and 0.7 (H2O2), with W = k·[PN]0.3·[H2O2]0.7, k = (3.69±0.11)·10-4 s-1 and τ₁/₂ = 31.1±0.30 min. For PN–H2O2–Cu(II), the partial reaction orders are 0.2 (PN), 0.4 (H2O2), and 0.3 (Cu2+) with k = (3.91±0.17)·10-4 s-1, and τ₁/₂ = 29.2±0.53 min. In conclusion, PN undergoes measurable photodegradation under simulated natural conditions.